Damage and repair of the axolemmal membrane: from neural development to axonal trauma and restoration - Quintá, Héctor R. (2019)
Fil: Quintá, Héctor R. Hospital Alemán. Laboratorio de Medicina Experimental Dr. J. Toblli; Argentina